2014
DOI: 10.3109/14647273.2014.912762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients’ questions to identify gaps in information provision to infertile patients

Abstract: The objective of this observational study was to identify gaps in written patient information at an infertility clinic, by systematically analysing the questions raised by infertile patients in a forum or during 'phone and group consultations. This was done (1) by identifying themes raised by patients undergoing Medically Assisted Reproduction and (2) by determining to what extent the questions asked by patients were absent from information leaflets provided by the clinic. A total of 193 questions were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Furthermore, these topics cover themes that seem to lack in traditional patient information leaflets or in face-to-face encounters [23], implying the value of the forum as an additional information channel.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these topics cover themes that seem to lack in traditional patient information leaflets or in face-to-face encounters [23], implying the value of the forum as an additional information channel.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that evidence-based information in various formats (eg, fact sheets, trusted websites, and podcasts) could help women with polycystic ovary syndrome make informed decisions about childbearing and achieve their reproductive goals. Van De Belt et al [ 12 ] analyzed questions in online forums and phone consultations to examine the gaps in information provision to infertile Dutch patients. The results showed that infertile patients demand high-quality health information and the information from health care providers did not cover all reported consumer information needs.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that infertile patients demand high-quality health information and the information from health care providers did not cover all reported consumer information needs. Hence providers should explore new means of health information creation that involve the patient perspective [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for patients to seek information on forums could be because of inadequate information provision channels (eg, verbal or written folders) provided by professionals or inadequate informational content in existing materials. Van de Belt et al [ 25 ] analyzed whether the questions patients asked on an online forum could be answered with the information that was provided in the patient folders. About half of the patients’ questions could not be answered with the information from the patient folders.…”
Section: Discussionmentioning
confidence: 99%